Pengaruh Latihan Target Cone dan Ban terhadap Hasil Ketepatan Shooting Jarak 9 Meter pada Atlet Petanque Di Kabupaten Brebes - Vebriana Khofifah; Maftukin Hudah; Bertika Kusuma (Ridwan Institute, 2021)
Petanque is a form of sports game that aims to throw an iron ball closer to the wooden ball. This study aims to determine how much influencetarget training has cone and tireon the results ofaccuracy shooting at 9 meters forathletes Petanque Brebes. In this research, the type of research used is quantitative research with the research method of Quasi Experimental Design. While the research design used Two Groups Pretest-Posttest Design. The sample used was 8 athletes Petanque Brebes Regency. The results showed that the increase in targettraining cone and tireto the results of theaccuracy of shooting 9 meters based on the results of the calculation of thetable Test of Homogeneity of Variances obtained the value of Sig = 0.069. Homogeneity with a significance level of 5% or 0.05, indicates that the Sig value is 0.069> 0.05, so for the overall hypothesis variable Ho: accepted. The conclusion of this study is the effect of targettraining cone and tireon the results of the accuracy of shooting a distance of 9 meters at Petanque athletes in Brebes Regency.